-5(2x+10)=6(-3x+20)

Simple and best practice solution for -5(2x+10)=6(-3x+20) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(2x+10)=6(-3x+20) equation:


Simplifying
-5(2x + 10) = 6(-3x + 20)

Reorder the terms:
-5(10 + 2x) = 6(-3x + 20)
(10 * -5 + 2x * -5) = 6(-3x + 20)
(-50 + -10x) = 6(-3x + 20)

Reorder the terms:
-50 + -10x = 6(20 + -3x)
-50 + -10x = (20 * 6 + -3x * 6)
-50 + -10x = (120 + -18x)

Solving
-50 + -10x = 120 + -18x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '18x' to each side of the equation.
-50 + -10x + 18x = 120 + -18x + 18x

Combine like terms: -10x + 18x = 8x
-50 + 8x = 120 + -18x + 18x

Combine like terms: -18x + 18x = 0
-50 + 8x = 120 + 0
-50 + 8x = 120

Add '50' to each side of the equation.
-50 + 50 + 8x = 120 + 50

Combine like terms: -50 + 50 = 0
0 + 8x = 120 + 50
8x = 120 + 50

Combine like terms: 120 + 50 = 170
8x = 170

Divide each side by '8'.
x = 21.25

Simplifying
x = 21.25

See similar equations:

| 100-53.25= | | g(v)=cosv/cscv | | CosV/CscV | | 2(x+5)=-3(x+10) | | w^2+6w+11=0 | | Tan31=x/3 | | x^2+2ax+(a+6)=0 | | X^3-6x^2=63504 | | 85=7+5x | | 2m^2+3m-17=0 | | u(x)=e(-0.1x) | | 6a+b=0 | | 6(4y-5)=5(11-2y) | | 5(15+a)=4(3-4a) | | 4(m+10)=3(8-4m) | | 5(6y-4)=2(3y+14) | | p^2+2pr+r^2-16= | | 2(5x-1)=7(3x-5) | | 6(3m+7)=30 | | 3(2w+4)=54 | | 2(7u-3)=50 | | 5(3p+6)=105 | | 2(5y-4)=12 | | t-4/7=5 | | 1000x^3-1y^6= | | x-(x*0.015)=150 | | x-(x*0.15)=150 | | 2x(2x+8)=0 | | 2x(2x+8)=960 | | 4/8=34 | | X-x*0.10=300 | | m=2.5+0.5n |

Equations solver categories